Up take, transportat and use of macronutrients in rootstock for star fruit tree cultivated in nutrient solutions - Rozane, Danilo Eduardo [UNESP] (2007)
The nutritional status of plants cultivated in nutrient solutions way be influenced by the solution which would affect its growth plants. The present essay was undergone to assess the nutritional demands of root stock for star fruit trees, cultivated in four different nutritional solutions. An completely experimental design was used with three repetitions, with four different nutrient solutions as treatments. The Hoagland & Arnon solution was used as standard and was the control wich was with compared three other solutions. The experiment was carrie out under green house conditions, using 8 L pot. After 150 days of transplantation, dry material and macro nutrient levels were determined. The following indicators were calculated: absorption efficiency; transportation efficiency, and efficiency of nutrient use. The Sarruge, the Castellane & Araújo, and the Furlani nutrient solutions were similar to accumulation of dry material in the star fruit plants. The use of the Hoagland & Arnon solution resulted in lower material dry production in and also lower of Ca and Mg use. Nutrient transportation efficiency was the indicator most affected by the different nutritional solutions used, while efficiency of nutrient use showed small variation when comparing the solutions.